SYNTHESIS OF LAxSR1-xTIO3 ANODE MATERIALS BY SOL-GEL AUTO-COMBUSTION METHOD - CHENG,JIHAI (Sociedad Chilena de Química, 2012)
A novel anode material for intermediate temperature solid oxide fuel cells with a composite of La xSR1-xTiO3 has been synthesized by a sol-gel auto-combustion method. X-ray diffraction (XRD) shows that La xSR1-xTiO3 has good chemical compatibility with Gd0.2 Ce0.8O1.9 electrolyte. The thermal expansion coefficient (TEC) of the as-prepared anode material is similar to that of Gd0.2 Ce0.8O1.9. The electric conductivity measurements show that the conductivity of La xSR1-xTiO3 increases with the increasing of lanthanum contents and reached a maximal value at x=0.3. At 800ºC, the electrical conductivity of La0.3Sr0.7TiO3 is 184Scm-1.